Effects of Vaccination Against the H1N1 Virus on BDNF and TNF-α Plasma Levels in Pregnant Women - Dias, Fernando M.V.; Diniz, Mirla F.; Franco, Glaura C.; de Miranda, Aline Silva; Teixeira, Antonio Lucio; Nunes, Poliana Toledo; Ribeiro, Angela Maria (Current Drug Safety, 2018)
Background: Vaccination is a widespread strategy to protect women and their children during fetal development. However, there is a lack of knowledge about potential effects of H1N1 vaccination on concentration of cytokines that are important to mother's central nervous system functions and fetal neurodevelopment. Objective: The main purpose of the present study was to evaluate such interaction. The specific goals were to study the effects of vaccination against the H1N1 virus on plasma levels of the Brain Derived Neurotrophic Factor(BDNF), Tumor Necrosis Factor-α (TNF-α) and TNF-α Receptors 1 and 2 (sTNFR1; sTNFR2), in different periods of gestation. Methods: Data were obtained during the period of 6 months in 2010, from a sample of 94 pregnant women who were using the health care service of Conceição do Mato Dentro, a rural area in the state of Minas Gerais, Brazil. Seventeen women were in the first trimester of pregnancy, forty were in the second trimester and 37 were in the third trimester. Each of these groups was divided into two subgroups as follows: immunized against the H1N1 virus (I) and non-immunized (NI). Plasma concentrations of BDNF, TNF-α, sTNFR1 and sTNFR2 were measured using the sandwich ELISA. Results: There was no difference in cytokine or neurotrophic factor levels evaluated between groups I and NI in any trimesters. Conclusion: These results show that the recommendation of vaccination against the H1N1 virus for all pregnant women as a public health measure could be considered safe, regarding aspects related to the role played by neurotrophin and cytokine, such as those of CNS development and immunological functions.
Keywords: Vaccination